Canons and Networks. 19th-Century Danish Art in Paris - Łukasiewicz, Martyna; Mednick, Thor (Artium Quaestiones, 2023)
Collections of Danish Golden-Age art are quite rare outside of Scandinavia, especially when it comes to those developed in accordance with a well-thought-out strategy established through the international cooperation of scholars. An important exception is the large group of Danish drawings, oil sketches, and artists’ correspondence found in the Fondation Custodia – Collection Frits Lugt in Paris, gathered by art historian and longtime museum director Carlos van Hasselt (1929–2009). As director, van Hasselt provided an interesting model of collecting, as his pursuit was not motivated by a particular investment strategy. His collection may, in a sense, be viewed as the material result of a network, one which he established and which brought together Danish researchers and museologists, as well as international art dealers. The aim of this article is therefore to investigate how a network may inform and help determine a particular collection practice, to trace how van Hasselt became an agent of the Danish art establishment, and to provide a critical overview of this collection, which became a satellite representation of the canon of 19th-century Danish art in Paris. Analysis of Carlos van Hasselt’s archive will provide critical reflections on the ways in which the collection was built and developed, and how it may serve as an example of the international dissemination of canons.